Aspectos da Biblioteconomia e Ciência da Informação para a privacidade de dados e ambientes digitais - Santos, Raniel Alessandro Andrade (Universidade Federal de São Carlos, 2022)
The false sense of security that the users have regarding their personal data makes them even more vulnerable to several types of fraud, from leaks to its commercialization. In addition, questions regarding privacy arise as a broad concept inside and outside technology as time goes by. With that in mind, laws have been created for data protection, to ensure user’s privacy. Thus, this study is dedicated to discuss data privacy, focusing on digital games and environments and analyzing the role played by data protection laws in the security of each individual’s personal data towards companies and organizations. Here, the national academic scope of this subject will be explored. From this perspective, the following research problem is incited: Does the data provided to companies while their services are being used remain, in fact, private? Focusing on this research problem, the aim of this study is to identify how data privacy work, from the Librarianship and Information Science perspective. For the investigative purpose, this study is a theoretical research classified as qualitative investigation and, regarding its procedures, it is a bibliographical research. Initially, theoretical research was carried out to substantiate the aspects of the current legislation, data privacy and security. As a result, the bibliometric analysis revealed that research about data privacy has increased over the years, however, more studies are needed regarding the data privacy of digital games and environments.
Aspects of library and information science for data privacy and digital environments
Keywords: Proteção de dados pessoais; Lei de acesso à informação; Privacidade; Proteção de dados; Dados pessoais; Lei geral de proteção de dados pessoais; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA